Pipeline robots with elastic elements - Matuliauskas, Arvydas; Spruogis, Bronislovas (Transport, 2002)
In the article constructions of the pipeline robots with elastic elements are reviewed and the scheme of new original construction is presented. The mathematical models of a robot with one-dimensional vibration exciter with two degrees of freedom were developed and the equations of movement were formed and written. The mathematical model of the pipeline robot with circular elements is formed and its motion equations are presented.First Published Online: 19 Dec 2011